The Effect of Herding Behavior on Millennial Generation Intentions in Investing Crypto Assets - Gede Wisnu Saputra; Agus Fredy Maradona (International Journal of Social Science and Business, 2023)
More and more millennials are interested in investing in crypto assets like Bitcoin and Ethereum. However, there is still uncertainty and hesitation in making this investment. This study aims to determine the effect of herding behavior on the millennial generation's intention to invest in crypto assets. This research was conducted in Indonesia with the respondents being the millennial generation who adopted crypto assets. The population in this study is the millennial generation of crypto asset adopters throughout Indonesia which continues to change every time, so the number is unknown. The sampling technique was carried out by purposive sampling with a sample of 220 respondents. Data was collected by distributing questionnaires via google form. The analysis used is SEM-PLS. The results of this study indicate that herding on social media environment has a positive and significant effect on behavioral intention. Herding on social media environment has a positive and significant effect on financial literacy. Herding on social media environment has a positive and significant effect on E-trust. Financial literacy has a positive and significant effect on behavioral intention. E-trust has no effect on behavioral intention. Ethical concern is able to moderate the influence of herding on social media environment on behavioral intention.